Corneal topographic indices of scheimpflug camera in type 2 diabetic and non-diabetic elderly populations - Alireza Hashemi; Mehdi Khabazkhoob; Foroozan Narooei; Abolghasem Mortazavi; Hassan Hashemi (BMC Ophthalmology, 2023)
Abstract Purpose The present study was conducted to determine the corneal topographic indices of Scheimpflug camera in type 2 diabetes patients without diabetic retinopathy (DR), DR and non-diabetic elderly populations. Methods A total of 1105 participants were selected using random cluster sampling from Tehran, Iran and categorized into three groups including type 2 diabetes patients without diabetic retinopathy (DR), DR and non-diabetic. The diabetic group had HbA1c levels ≥ 6.4% with no other systemic problems. The non-diabetic participants had normal eye findings and no systemic diseases. The pachymetric progression index (PPI) values were measured using the Pentacam AXL. Results A total of 1105 participants including 429 diabetes patients (38.46% male) and 676 non-diabetic (38.76% male) subjects entered the study. Only PPIavg and PPImax were higher in the diabetics versus non-diabetics (P = 0.019 and 0.010, respectively). There was a significant difference in PPImax between the three groups (P = 0.036). There were significant differences only in index of vertical asymmetry (IVA), central keratoconus index (CKI), PPI average, and PPI max between different stages of diabetic retinopathy (DR) (P = 0.045, 0.005, 0.002, and 0.004, respectively). There was a significant difference in index of Surface Variance (ISV), index of vertical asymmetry (IVA), PPIavg, and PPImax between diabetes patients with and without DR (P = 0.016, 0.022, < 0.001, and < 0.001, respectively). Conclusion According to the results, diabetes and DR change several topographic indices. In addition, the HbA1c level may affect pachymetric progression index max. Therefore, special attention should be paid to these patients for different treatment strategies.